Qurain AL-Thamad Valley Hydrological Aspects Extraction Using Remote Sensing and GIS Techniques - azeez, laith (Iraqi Journal of Science, 2019)
In the arid to semi-arid lands the extracted hydrological features are essential ones, since their effect on water projects managing, agricultural projects administrating, and animals grazing, so that this research is considered to be vital research because the climate of Qurain AL-Thamad basin is arid climate and basin region inhabited by many tribes who works in agricultural and grazing fields. The illustration of hydrological features using morphometric analyses is optimum since the quantization issue of basin factors, in the past this would be difficult using classical procedures (i.e. using paper topographic maps and planmeter). Recently as in this work modern procedures has been used (i.e. satellite imagery DEM as ancillary image and Arc GIS 10.5 as geo-measuring and spatio-analyzing program). The pattern of Qurain AL-Thamad basin’s drainage network shows dendritic configuration in low orders streams and parallel configuration in the high order streams. The spatial analysis using GIS environment categorize basin’s shape parameters into three categories: firstly one is the linear parameters with streams divided into 1st order streams with (611.587 km) length, 2nd order streams with (384.015 km) length, 3rd order streams with (181.868 km) length, and 4th order streams with (103.674 km) length. Bifurcation ratios were calculated, Rb1 is (2.046), Rb2 is (1.869), and Rb3 is (1.624), with (1.852) Rb mean value. Secondly categorize deals with areal parameters; The longitudinal drainage density was (0.259 km??), the drainage frequency was (0.035 stream /km²), Drainage Texture value was (0.338 stream / km ), the elongation ratio was (0.483), the circularity ratio value was (0.244), the form factor was (0.183) , and the relief ratio was (0.447). according to these quantitative results the flood hazard in the basin main stream is absent, basin soil is high permeable and region rainfall rate is very low, there is significant differences in region geological structures solidity, land steepness and relief ratio are low valued yielding a few water erosion power, sediment yield, and runoff flood peak in the basin water catchment area.